Speed Runner S.A. - Tateishi, Víctor (2001)
The case presents a production company that intends to maintain its distribution and sales policies in a context of recession. In this sense, it is presented for discussion and exchange of ideas. In the middle of the discussion, it would be interesting to be able to differentiate what is a policy decision from what is the real market situation.